Kudûrî'nin umûm anlayışının hadis yorumuna etkisi (et-tecrîd'in tahâret bölümü örneği) - Öztürk, Aykut (My University, 2023)
Bu çalışmada, öncelikle hicrî V. asrın Bağdat’ında yaşayan ve daha ziyade fakih kimliğiyle tanınan Ahmed b. Muhammed Ebü’l-Hüseyn el-Kudûrî’nin (ö. 428/ 1037) ilmî şahsiyeti ve hadis ilmine dair bazı değerlendirmeleri incelenmiş, ardından benimsediği umûm anlayışının hadis yorumundaki etkisi araştırılmıştır. Bu amaçla Kudûrî’nin kaleme aldığı ve Hanefî mezhebinde önemli bir konuma sahip olan et-Tecrîd adlı eserinin tahâret bölümünde umûm kapsamında değerlendirdiği hadislerin sübûtu ve delâleti irdelenmiştir. Bu araştırmada Kudûrî’nin et-Tecrîd’inde mana ve maksat eksenli hadis yorumunun yanı sıra Arap dil kurallarına dayalı lafız ağırlıklı bir yaklaşım tarzının da olduğu görülmüştür. Nitekim Kudûrî ve diğer Irak Hanefî fakihleri tarafından benimsenen ve nasları anlama ve yorumlama yöntemi olarak kullanılan umûm anlayışı, yoğunlukla Ehl-i hadîs taraftarlarınca önemsenen zâhirci ve lafızcı bir hadis yorumuna yol açmıştır. Buna rağmen Kudûrî’nin, yeri geldiğinde hadislerin dilsel unsurlarını bir kenara bırakarak farklı unsurları nazarı itibara alması onun, lafız-mana dengesini korumaya özen gösterdiğini ve lafızcı tavrının, re’y ve akıl yürütmekten tamamen soyutlanmadığını göstermektedir. İsnad, cerh-ta‘dîl ve ilel gibi hadis ilmine ilişkin teknik meselelerde Abdurrahman b. Mehdî (ö. 198/ 813), Abdullah İbnü’l-Mubârek (ö. 181/ 797), Yahyâ b. Maîn (ö. 233/ 848) ve Ahmed b. Hanbel (ö. 241/ 855) gibi önde gelen hadis münekkitlerinin görüşlerine başvuran Kudûrî, hadisleri yorumlama sırasında kendi geleneğine sıkı sıkıya bağlı kalmaktadır.

In this study, the scholarly personality of Abu al-Husayn al-Qudûrî, who lived in Baghdad in the 5th century AH and is known best by his identity as a jurist (faqih), and his evaluations related to the science of hadith were examined; following that, the effect of his understanding of umum on his interpretation of hadith was analyzed. For this purpose, the hadiths evaluated within the scope of umum in the purification (taharah) section of the work Al-Tajrīd, which was written by Qudûrî and possesses a valuable and esteemed status in the Hanafi school, were discussed in terms of indication (delalet) and authenticity. In this study, it is concluded that Qudûrî has aside from hadith interpretations centered on meaning and purpose, a wording-heavy approach based on the linguistic structure of the Arabic language. Because the concept of umum, which had its foundations established by Qudûrî and other Iraqi Hanafi jurists and is used as a method of understanding and interpreting religious texts, paved the way for a literalist interpretation valued mainly by Ahl al-Hadith adherents. However, Qudûrî’s dispensation with linguistic elements for the consideration of other elements shows both that he paid attention to preserving the balance between word and meaning and that his literalist side cannot be wholly abstracted from ra’y and ijtihad. On the other hand, whereas Qudûrî resorts to the judgments of leading hadith critics as such as Abdulrahman ibn Mahdi, Abdullah ibn Al Mubarak, Yahya ibn Ma’in and Ahmad ibn Hanbal on technical issues related to the science of hadith such as isnad, jarh-ta’dil and ‘ilal, he adheres strictly to his own tradition when interpreting hadiths.
Keywords: al-Tajrid; Ebü’l-Hüseyn Ahmed b. Ebî Bekr Muhammed b. Ahmed el-Kudûrî el-Bağdâdî (ö. 428/ 1037); et-Tecrîd; Hadis; Hadith; Hanafi; Hanefî; Kudûrî; Qudûrî; Umum; Umûm